Standardized Minimalistic Transfemoral Transcatheter Aortic Valve Replacement (TAVR) Using the SAPIEN 3 Device: Stepwise Description, Feasibility, and Safety from a Large Consecutive Single-Center Single-Operator Cohort. Issue 3 (4th July 2017) - Frangieh, Antonio H.; Ott, Ilka; Michel, Jonathan; Shivaraju, Anupama; Joner, Michael; Mayr, N. Patrick; Hengstenberg, Christian; Husser, Oliver; Pellegrini, Costanza; Schunkert, Heribert; Kastrati, Adnan; Kasel, Albert Markus
ABSTRACT: Background: To describe our updated minimalist approach (MA) for transfemoral transcatheter aortic valve replacement (TF-TAVR) using the SAPIEN 3 device and its evolution, as well as associated safety and efficacy parameters from a large cohort of patients. Methods: A stepwise description of the MA technique for TAVR for 300 consecutive patients was detailed. Safety and efficacy parameters were assessed using the VARC-2 criteria at the in-hospital and 30-days follow-up. Results: A total of 300 consecutive patients (80 ± 7 years; median Logistic EuroSCORE of 11.4% [7.5–17.8]) between January 2014 and May 2016 were evaluated. TF-TAVR was performed under conscious sedation in 247 (82%) patients. Device success was achieved in 286 (95.6%) patients, and intended prosthesis performance in 289 (96.3%) patients. Significant paravalvular leak (PVL) graded more than mild was noted in 7 (2%) patients. No patient had severe PVL. All-cause mortality was noted in one (0.3%) patient in-hospital and in 2 (0.7%) patients at the 30-days follow-up. Major stroke occurred in 4 (1.3%) patients. 9 (3%) patients had major vascular complications at 30-days follow up. MACCE (VARC-2 criteria) were observed in 21 (7%) in-hospital and 25 (8.3%) at 30 days. A new permanent pacemaker implantation was required in 29 (10.7%) patients, and was reduced from 18% to 5.6% ( p = 0.001) in a subgroup analysis considering higher implantation position of the valve after the first year of experience. Conclusion: MA of TF-TAVR, when simplified and standardized, is reproducible, safe and efficient, and should be encouraged to be accepted as the standard method of care.